2000
DOI: 10.1074/jbc.275.1.451
|View full text |Cite
|
Sign up to set email alerts
|

The Synaptic Vesicle Protein SV2 Is Complexed with an α5-Containing Laminin on the Nerve Terminal Surface

Abstract: Interactions between growing axons and synaptic basal lamina components direct the formation of neuromuscular junctions during nerve regeneration. Isoforms of laminin containing ␣5 or ␤2 chains are potential basal lamina ligands for these interactions. The nerve terminal receptors are unknown. Here we show that SV2, a synaptic vesicle transmembrane proteoglycan, is complexed with a 900-kDa laminin on synaptosomes from the electric organ synapse that is similar to the neuromuscular junctions. Although two lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 49 publications
1
40
1
Order By: Relevance
“…The observation that SV2 binds the extracellular matrix protein laminin suggested that SV2 could play a role in synapse formation (Carlson, 1996;Son et al, 2000). To determine whether reduced EPSC amplitude was attributable to reduced synapse formation, we compared synapse number in wild-type and SV2 knock-out neurons.…”
Section: Resultsmentioning
confidence: 99%
“…The observation that SV2 binds the extracellular matrix protein laminin suggested that SV2 could play a role in synapse formation (Carlson, 1996;Son et al, 2000). To determine whether reduced EPSC amplitude was attributable to reduced synapse formation, we compared synapse number in wild-type and SV2 knock-out neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Receptors presumably include integrins, which bind laminins generally; indeed, integrin ␣ 3 is concentrated at active zones (27). In addition, laminins-9 and -11 co-purify with distinct presynaptic membrane components, the calcium channels that trigger transmitter release and the vesicle-associated protein, SV2, respectively (58,59). These associations raise the possibility that laminins could organize presynaptic differentiation in part by direct interactions with critical components of the release apparatus.…”
Section: Differentiation Of Nerve Terminalsmentioning
confidence: 99%
“…The observation that SV2 binds the extracellular matrix protein laminin (8) suggested that it could participate in the formation of synapses or the establishment of active zones. To determine whether the reduced neurotransmission in SV2A knockouts is caused by changes in synapse density and͞or morphology, synapses were analyzed at the electron microscopic level.…”
Section: Inhibitory Neurotransmission Is Reduced In the Hippocampus Omentioning
confidence: 99%
“…The absence of SV2 homologs in yeast suggests that it is not a component of the basic membrane trafficking mechanism and, therefore, may mediate a process unique to regulated secretion. The structure and protein interactions of SV2 suggest multiple possible functions, which include acting as a transporter (3)(4)(5), providing a matrix for neurotransmitter concentration and release (7), acting as a receptor for extracellular matrix proteins (8), and regulating the action of other synaptic proteins (9). To explore the function(s) of SV2 in an in vivo context, we used the technique of targeted gene disruption to produce animals that do not express SV2A.…”
mentioning
confidence: 99%